A model ensemble approach to determine the humus building efficiency of organic amendments in incubation experiments. (2nd February 2021) - Gasser, Anton A.; Diel, Julius; Nielsen, Kerstin; Mewes, Paul; Engels, Christof; Franko, Uwe
Abstract: Organic amendments are important to sustain soil organic matter (SOM) and soil functions in agricultural soils. Information about the contribution of organic amendments to SOM can be derived from incubation experiments. In this study, data from 72 incubated organic amendments including plant residues, digestates and manure were analysed. The incubation data was compiled from three experimental setups with varying incubation times, soils and incubation temperatures, in which CO2 release was measured continuously. The analysis of the incubation data was performed with an approach relying on conceptual parts of C‐TOOL, CCB, Century, ICBM, RothC and Yasso which are all well‐approved first‐order carbon models that differ in structure and abstraction level. All models are an approximation of reality, whereby each model differs in understanding of the processes involved in soil carbon dynamics. To accumulate the advantages from each model a model ensemble was performed for each substrate. With the ability of each carbon model to compute the distribution of carbon into specific SOM pools a new approach for evaluating organic amendments in terms of humus building efficiency is presented that, depends on the weighted model fit of each ensemble member. Depending on the organic substrate added to the soil, the time course of CO2 release in the incubation studies was predicted with different accuracy by the individual model concepts. Averaging the output of the individual models leads to more robust prediction of SOM dynamics. The EHUM value is easy to interpret and the results are in accordance with the literature.